Enhanced Recovery in Surgery for Gastric Cancer - O. V. Ilyina; D. V. Ruchkin; I. A. Kozyrin; Yu. A. Stepanova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. A summarising review of national and international practices in enhanced recovery after surgery (ERAS) for gastric cancer.Key points. Although ERAS is a routine protocol in colorectal surgery, little agreement exists on its eﬀectiveness and safety in upper gastrointestinal surgery, particularly, for gastric cancer (GC). General recommendations are being widely followed in clinical practice, whilst the adherence to GC-speciﬁc measures is still limited. The review highlights the speciﬁc measures of perioperative nutrition, surgical approach, early postoperative diet, phase-out of routine nasogastric or nasojejunal tubes, audit of results. The GC-speciﬁc protocols include the early detection of postoperative complications, especially the oesophagojejunal anastomosis leakage, to facilitate the ERAS safety and early oral nutrition.Conclusion. Current evidence suggests a strong association of ERAS with improved outcomes and quality of life in the early postoperative period. The long-term impact of ERAS remains understudied but is expected to reduce complications and their severity in oncological surgery.